Tourism Opportunities of Jizzakh Region - Isamiddinovna, Kholmurzayeva Dilorom (PT. Antis International Publisher, 2024)
One of the promising sectors that bring high income to the national economy is tourism, which is one of the most dynamically developing sectors of the world economy. The comprehensive development of tourism is becoming a great source of income for many countries.